2015
DOI: 10.18632/oncotarget.3296
|View full text |Cite
|
Sign up to set email alerts
|

Combining lapatinib and pertuzumab to overcome lapatinib resistance due to NRG1-mediated signalling in HER2-amplified breast cancer

Abstract: Acquired resistance to lapatinib, an inhibitor of EGFR and HER2 kinases, is common. We found that reactivation of EGFR, HER2 and HER3 occurred within 24 hours of lapatinib treatment after their initial dephosphorylation. This was associated with increased expression of NRG1 in cells treated with lapatinib. Exogenous NRG1 partially rescued breast cancer cells from growth inhibition by lapatinib. In addition, both parental and lapatinib-resistant breast cancer cells were sensitive to SGP1, which inhibits binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Nrg1 encodes neuregulin 1 or heregulin, the predominant ligand for ERBB3, and NRG1/ERBB signals are important in cellular development such as for Schwann cells and the cardiovascular system . This signaling axis is also important in multiple cancer types and activation of the signal promotes cancer cell migration or drug resistance . Although the exact functions of TRIB1 and NRG1 in clinical cases of Ewing sarcoma remain to be clarified, the present study highlighted their potential roles as therapeutic targets and/or biomarkers.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Nrg1 encodes neuregulin 1 or heregulin, the predominant ligand for ERBB3, and NRG1/ERBB signals are important in cellular development such as for Schwann cells and the cardiovascular system . This signaling axis is also important in multiple cancer types and activation of the signal promotes cancer cell migration or drug resistance . Although the exact functions of TRIB1 and NRG1 in clinical cases of Ewing sarcoma remain to be clarified, the present study highlighted their potential roles as therapeutic targets and/or biomarkers.…”
Section: Discussionmentioning
confidence: 73%
“…Trib1 was identified as a leukemia disease gene that enhances MAPK phosphorylation and degrades C/EBPα . Nrg1 promotes tumor progression in many cancers such as gastric, lung, and breast cancers . Notably, these genes have been previously identified as EWS‐FLI1‐binding genes in human Ewing sarcoma .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have previously shown that trastuzumab induced an increase of ADAM10 and ADAM17 expression, which enhanced the release of the HER ligands betacellulin and heregulin (neuregulin), resulting in activation of HER receptors as well as downstream signaling pathways during prolonged treatment with trastuzumab 42,43. A ligand-dependent mechanism has also been reported in vitro with regard to lapatinib resistance 44,45…”
Section: Introductionmentioning
confidence: 95%
“…We have recently shown that neuregulin (NRG1) can counteract the response to lapatinib, which was improved by the combination of lapatinib with pertuzumab, an antibody binding to the HER2 dimerization domain 45. It would thus be interesting to test whether NRG1 mediates resistance to neratinib and whether pertuzumab could also enhance the response to neratinib.…”
Section: Introductionmentioning
confidence: 99%